Scientific excellence : (Sage Publications, 1987)
Contents: Scientific Excellence highlights the need for research into the processes that facilitate the generation, systematization and transmission of knowledge. The contributors -- eminent researchers in the field -- assess the present state of knowledge and give directions for future research. The book covers a variety of important issues concerning the creation and dissemination of knowledge.